The credibility of the information of Financial Journalism: how it influences in investment decisions made by private investors. A qualitative analysis. - Sánchez-Galán, José Ramón (Estudios sobre el Mensaje Periodístico, 2012)
This work tries to analyze whether economic information in newspapers is perceived as a credible source for individuals to make their investment decisions considering two main aspects: they have little knowledge in this matter and they do not have many resources to invest much money in financial products. In this way, we have focused our investigation on economic behaviours of “non experts” individuals and the reasons of their decisions which are, at last, based on journalistic financial information.
Keywords: Motivation; mutual funds; shares; personal interviews; group meetings.